How Adult Learners Change In Higher Education - Kathleen P. King (Adult Education Research Conference, 1998)
Research about the nature of the relationship between perspective transformation and education was conducted among 422 adult learners in higher education. This paper addresses the areas of change recognized, the formal stages of perspective transformation identified, the relationship of the experience in adult learners' education and the implications of the findings.